The Effect of Motivation, Training and Work Discipline on Employee Performance: The Case of CV. Bumi Angkasa Sejahtera South Sumatera - stefani, Putri (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This study examines the effect of motivation, training, and work discipline on employee performance at CV. Bumi Angkasa Sejahtera South Sumatra. The object of the study is CV Bumi Angkasa Sejahtera South Sumatra. Address Jalan Tanjung Sari I, Jl. Sapta Marga No. 1A, Bukit Sangkal, Kec. Kalidoni, Palembang City, South Sumatra 30114. This study is a causal associative study using a quantitative approach. The dependent variable is performance, with indicators of work quality, work quantity, and responsibility. The independent variables are motivation, training, and work discipline. The indicators of motivation are the need for security, the need to feel belonging, and the need for self-esteem. The training indicators are participants, materials, and objectives. The indicators of work discipline are obedience to time rules, company regulations, and rules of conduct at work. The population used in this study were all CV Bumi Angkasa Sejahtera South Sumatra employees, totaling 135 people, and the sample consisted of 100 respondents. The method used in data collection was a questionnaire, The analysis model used was multiple linear regression. The result reveals that motivation, training, and work discipline positively and significantly affect CV employee performance. Bumi Angkasa Sejahtera South Sumatera